Assessing the Impact of Oil Price Volatility on Nigeria's Economic Growth and Stability 2006 to 2022: a Quantitative Analysis - Augustine Okon Jacob Jacob; Okon Joseph Umoh Umoh (MultiTech Publisher, 2023)
This research use time series analysis to examine Nigeria's economic dynamics, concentrating on the link between Real Gross Domestic Product (RGDP), Inflation (IFR), Interest (INT), and Crude Oil Price. The information covers the years 2006 to 2022 and gives insights into how the country has changed over time. The results show a positive trend in RGDP, indicating economic expansion. Inflation rates vary, suggesting the presence of both inflationary and deflationary influences. Interest rates are constant, while crude oil prices are volatile, affecting Nigeria's oil-dependent economy. A somewhat positive association between Crude Oil Price and independent variables is revealed using regression analysis. The statistical significance of the independent variables, on the other hand, is only slightly supported. The ANOVA table validates the regression model's overall significance, indicating an influential independent variable. The influence of independent factors on the dependent variable is demonstrated by coefficients, but their significance falls short of traditional values. The correlation matrix reveals an inverse link between RGDP and output/crude oil exports. There are weak positive connections between RGDP and inflation, as well as crude oil prices and inflation. Interest rates and crude oil exports do not have a strong relationship with crude oil prices. These findings helped to comprehend Nigeria's economic dynamics and illustrate the complexities of varied interactions. To go deeper into certain hypotheses, more study is required. The study emphasizes the significance of understanding the impact of oil price changes on the Nigerian economy in order to drive appropriate policy responses and the necessity for economic diversification.